Comparison of Physiological Effects of Using Face Mask and Personal Protective Equipment (PPE) during Six-Minute Walk Test among Healthy Adults – A Pilot Study - Padmavathy K.M; Noorzaid Bin Muhammad; Rohith Sharan S; Siti Nur Rasinah Binti Abdullah (Asian Journal of Medicine & Health Sciences, 2023)
Introduction: Since the beginning of COVID-19, speculation surrounding the usage of masks or PPE (Personal Protective Equipment) affecting the physiologic parameters is widespread. This pilot study is part of a bigger study that tries to explore the differences in the physiologic parameters when wearing respirator protection, before and after a validated six-minute walk test (6-MWT), which is a sub-maximal exercise test used to assess aerobic capacity and endurance. Aim: To compare the changes in the physiological parameters of using a facemask (N95) and PPE assessed by a (6-MWT). Materials and methods: This study followed a three-group quasi-experimental panel design. Nine subjects, aged between 18 to 50 years, who have received both doses of the COVID vaccine and residing in Ipoh, Perak participated in this study. The participants were randomly assigned into three groups (Control, Face mask, and PPE). Participants’ heart rate, blood pressure, oxygen saturation (SpO2), and aural temperature were recorded. A 6-MWT was chosen for its relevant environment and physical exertion that of a general population. A comparative analysis was done by one-way ANOVA. Results: The differences in the physiological parameters between the control, face mask, and PPE groups, before and after walking for 6 minutes were not significant. The mean walking distance was not different among the three tested groups. Conclusion: A 6-MWT was sufficient to explore the effects of a face mask and PPE in a setting similar to that of the general population. Adopting protective measures such as face masks or PPE does not change the normal physiological parameters and has a greater public health significance in the prevention and control of infectious respiratory diseases.